1992
DOI: 10.1007/bf01930468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dipyridamole and adenosine monophosphate on cell proliferation in the hemopoietic tissue of normal and gamma-irradiated mice

Abstract: Combined treatment with dipyridamole and adenosine monophosphate enhances cell proliferation in the hemopoietic tissue of normal and gamma-irradiated mice. This effect can be explained by the elevation of extracellular adenosine, and the receptor-mediated activation of the cell adenylate cyclase system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Survival of animals irradiated with absolute lethal doses under this drug treatment regimen has been evaluated, as well. These experiments confirmed the protective action of dipyridamole and AMP combination under conditions of single [ 23 , 27 , 28 , 29 ] and also fractionated irradiation [ 30 , 31 ]. These effects are most probably due to the modulation of regulatory functions, i.e.…”
Section: Hematological Effects Of Non-selective Activation Of Adensupporting
confidence: 61%
See 2 more Smart Citations
“…Survival of animals irradiated with absolute lethal doses under this drug treatment regimen has been evaluated, as well. These experiments confirmed the protective action of dipyridamole and AMP combination under conditions of single [ 23 , 27 , 28 , 29 ] and also fractionated irradiation [ 30 , 31 ]. These effects are most probably due to the modulation of regulatory functions, i.e.…”
Section: Hematological Effects Of Non-selective Activation Of Adensupporting
confidence: 61%
“…It should be noted that doses of dipyridamole and AMP used in the experiments described in this review exhibit significant pharmacological effects at low toxicity [ 22 ]. The efficiency of the combined action of the drugs compared to their action when given alone has been verified [ 23 ].…”
Section: Hematological Effects Of Non-selective Activation Of Adenmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of dipyridamole (DP), a drug inhibiting the cellular uptake of adenosine [ 154 ], and adenosine monophosphate (AMP), an adenosine prodrug [ 155 ], has been used in an attempt to enhance the receptor action of adenosine in a series of studies on irradiated mice. The results of these studies have clearly shown that the pre-irradiation combination of DP and AMP stimulates hematopoiesis and increases survival under conditions of single [ 156 , 157 , 158 , 159 ], as well as fractionated irradiation [ 159 , 160 ].…”
Section: Other Compounds Tested As Radioprotectors or Radiomitigatmentioning
confidence: 99%
“…Adenosine receptors, activated non-selectively in the experiments mentioned [ 155 , 156 , 157 , 158 , 159 , 160 ], exist in four subtypes. Further experimentation, using agonists selected for the individual subtypes, has been aimed at finding out whether stimulation of one of the four subtypes is responsible for the previously observed hematopoiesis-stimulating and radioprotective effects.…”
Section: Other Compounds Tested As Radioprotectors or Radiomitigatmentioning
confidence: 99%